Photon Synthesis of Nanometric Films Based on Transitional Metal oxides for Multi-Parameter Sensors - Mulenko, S.A.; Luches, A.; Caricato, A.P.; Valerini, D. (ALT Proceedings, 2026)
The reactive pulsed laser deposition (RPLD) based on a KrF laser was used for photon synthesis of nanometric iron and chromium oxides films. RPLD allows controlling the thickness and stoichiometry of deposits with definite band gap. So RPLD was used for synthesizing nanometric iron and chromium oxides films for thermo-photo-chemical sensors. We compared sensing properties of iron and chromium oxides nanometric films deposited on <100>Si substrate by RPLD. These iron and chromium oxides films have semiconductor properties with the band gaps less than 1.0 eV. The largest photosensitivity of iron and chromium oxides films was about 44 Vc/W and 2.5 Vc/W, accordingly, for white light at power density 6x10-3 W/cm2. Vc is “chemical” photo e.m.f.. Maximum value of thermo electromotive force (e.m.f.) coefficient of iron and chromium oxides films was about 1.65 mV/K and 3.5-4.5mV/K, accordingly. Iron oxides films were tested as chemical sensors: the largest sensitivity of NO molecules was at the level of 7x1012 cm-3. Our results showed that nanometric iron and chromium oxides films synthesized by UV photons can be used as up-to-date materials for multi-parameter sensors operating at moderate temperature.